2018
DOI: 10.3390/coatings8110393
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Corrosion Resistance of WC-Based Cermet/Fe-Based Amorphous Alloy Composite Coatings

Abstract: There is an urgent need to improve the corrosion resistance of WC-based cermet coatings in different corrosive environments. The main objective of this work was to investigate the microstructure and evaluate the corrosion resistance in neutral, acidic, and alkaline electrolytes of the WC-based cermet/Fe-based amorphous alloy composite coating. Thus, a composite coating of WC-CoCr/Fe-based amorphous alloy and a single WC-CoCr coating were fabricated using the high-velocity oxygen fuel (HVOF) process. The phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
(35 reference statements)
1
5
0
Order By: Relevance
“…Additionally, in the C3 coating, the Cr 3 C 2 (PDF#00-035-0804) and Cr 7 C 3 (PDF#00-036-1482) carbides have been identified. Moreover, crystallites were detected in the C2 coating in the presence of cubic W (PDF#00-001-1204), which is in agreement with literature data [ 40 ]. It should be noted that no peaks coming either from the WC 1-x phase or from the Co 3 W 3 C or Co 6 W 6 C phases were found in the coatings, but those phases were identified in other papers and feedstock powders ( Figure 15 ) [ 24 , 41 , 42 , 43 ].…”
Section: Resultssupporting
confidence: 91%
“…Additionally, in the C3 coating, the Cr 3 C 2 (PDF#00-035-0804) and Cr 7 C 3 (PDF#00-036-1482) carbides have been identified. Moreover, crystallites were detected in the C2 coating in the presence of cubic W (PDF#00-001-1204), which is in agreement with literature data [ 40 ]. It should be noted that no peaks coming either from the WC 1-x phase or from the Co 3 W 3 C or Co 6 W 6 C phases were found in the coatings, but those phases were identified in other papers and feedstock powders ( Figure 15 ) [ 24 , 41 , 42 , 43 ].…”
Section: Resultssupporting
confidence: 91%
“…Yasir et al [369,370] examined the impact of Al 2 O 3 addition on corrosion properties of Fe-based MGC (Figure 60b) and found that the composite coatings were free from any galvanic corrosion effect. Further, Xu et al [371] investigated the corrosion performance of WC/Fe-based MG composite coating and found superior corrosion properties for composite coating in NaCl solution (Figure 60c), but degraded properties in an HCl environment.…”
Section: Ex-situ Composite Coatingsmentioning
confidence: 99%
“…Yasir et al [369,370] examined the impact of Al 2 O 3 addition on corrosion properties of Fe-based MGC (Figure 60b) and found that the composite coatings were free from any galvanic corrosion effect. Further, Xu et al [371] investigated the corrosion performance of WC/Fe-based MG composite coating and found superior corrosion properties for composite coating in NaCl solution (Figure 60c), but degraded properties in an HCl environment.
Figure 60. Corrosion properties of different ex-situ Fe-based MG composite coatings: Polarization plots of Fe-based MG composite coatings; (a) with and without TiN addition [368], (b) containing various weight fractions of Al 2 O 3 phase [369] and (c) as-sprayed WC–CoCr and composite coatings [371], in 3.5% NaCl solution. Cited images have been reproduced with due permission from the publishers.
…”
Section: Fe-based Metallic Glass Composite Coatings: Optimization Of ...mentioning
confidence: 99%
“…Hydraulic machinery working in the Yellow River is inevitably eroded by sediment. Traditionally, these components are fabricated of stainless steel [1,2], when sand grains impact the surface of the flow components, the strong deformation work drives the material to deform or crack off, and consequently caused the wear of the material [4], naturally then, the efficiency and service life of hydraulic machinery are reduced [2,5,6], which causing significant economic losses. Therefore, it is necessary to coat the components with coatings which exhibit excellent wear resistance.…”
Section: Introductionmentioning
confidence: 99%